Reading Readiness Skills in Preschool Children (Journal of the College of Education for Women, 2019)
This research aims to identify the following :The reading willingness skill to kindergarten children.There is no statistical significance difference between average scores of reading willingness skill of the sample individuals as a whole, and the hypothetical average of the scale.The difference in reading willingness skill to kindergarten children according to gender variable (male & female).There is no statistical significance difference between average scores of reading willingness skill for kindergarten children according to gender variable (male & female). To achieve the research goals, the researcher adopted the test of (Alkhafa-2014) for reading willingness skill, as it's consisted of seven skills: Visual recognition, Audio recognition, Audiovisual recognition, Optical recognition, Audio memory, Visual tracking, pronunciation and speaking skill.